Programa de inclusión intergeneracional: Conservación de saberes ancestrales entre adultos mayores y estudiantes de quinto año de EGB de la Escuela de Educación Básica Nueve de Octubre de la Comunidad de Sanjapamba, Parroquia San Andrés, Cantón Guano durante el año lectivo 2021-2022. - Paguay Duchi, Vilma Verónica (2022)
ABSTRACT: The present research work is called intergenerational inclusion program: Conservation of ancestral knowledge between older adults and children of fifth grade, basic general education. The objective of this research was to elaborate on a program of intergenerational inclusion preserving ancestral knowledge, ancestral games, and ancestral medicine. Its methodology was mixed. The design is non-experimental because it based fundamentally on the observation of phenomena as they occur in their natural context, an ethnographic type of research. After all, the study is of the social context, and bibliographic because it was necessary to review various bibliographic sources, descriptive level because it allowed to observe and detail the reality as the phenomenon presented, the total population was 73 people, the techniques were observation whose instrument is the observation sheet, the in-depth interview with its instruments, interview guide. These data were organized, analyzed, and interpreted, the same that served as unequivocal information for the elaboration of the program, intergenerational inclusion, increasing social relations between different generations, promoting solidarity, helping social participation and inclusion, decreasing feelings of loneliness, breaks stereotypes about old age and enhances active aging. Key words: intergenerational inclusion, older adults, childhood, ancestral knowledge.